Effects of a multicomponent resistance-based exercise program with protein, vitamin D and calcium supplementation on cognition in men with prostate cancer treated with ADT: secondary analysis of a 12-month randomised controlled trial. Issue 6 (24th June 2022) - Mundell, Niamh Liana; Owen, Patrick J; Dalla Via, Jack; Macpherson, Helen; Daly, Robin; Livingston, Patricia M; Rantalainen, Timo; Foulkes, Stephen; Millar, Jerremy; Murphy, Declan G; Fraser, Steve
Abstract : Objectives: The aim of this preplanned secondary analysis of a 12-month randomised controlled trial was to investigate the effects of a multicomponent exercise programme combined with daily whey protein, calcium and vitamin D supplementation on cognition in men with prostate cancer treated with androgen deprivation therapy (ADT). Design: 12-month, two-arm, randomised controlled trial. Setting: University clinical exercise centre. Participants: 70 ADT-treated men were randomised to exercise-training plus supplementation (Ex+ Suppl, n=34) or usual care (control, n=36). Intervention: Men allocated to Ex + Suppl undertook thrice weekly resistance training with weight-bearing exercise training plus daily whey protein (25 g), calcium (1200 mg) and vitamin D (2000 IU) supplementation. Primary and secondary outcome measures: Cognition was assessed at baseline, 6 and 12 months via a computerised battery (CogState), Trail-making test, Rey auditory-verbal learning test and Digit span. Data were analysed with linear mixed models and an intention-to-treat and prespecified per-protocol approach (exercise-training: ≥66%, nutritional supplement: ≥80%). Results: Sixty (86%) men completed the trial (Ex + Suppl, n=31; control, n=29). Five (7.1%) men were classified as having mild cognitive impairment at baseline. Median (IQR) adherence to the exercise and supplement was 56% (37%–82%) and 91% (66%–97%), respectively. Ex + Suppl had no effect on cognition at any time. Conclusions: A 12-month multicomponent exercise training and supplementation intervention had no significant effect on cognition in men treated with ADT for prostate cancer compared with usual care. Exercise training adherence below recommended guidelines does not support cognitive health in men treated with ADT for prostate cancer. Trial registration number: Australian and New Zealand Clinical Trial Registry (ACTRN12614000317695, registered 25/03/2014) and acknowledged under the Therapeutic Goods Administration Clinical Trial Notification Scheme (CT-2015-CTN-03372-1 v1).